Policing the borders within - Aliverti, Ana J. (Oxford : Oxford University Press, 2021)
'Policing the Borders Within' offers an in-depth, comprehensive exploration of the everyday working of inland border controls in Britain, informed by extensive empirical material viewed through the lens of wide-ranging interdisciplinary debates. In particular, this book examines afresh the relationship between policing, borders, and social order, in terms of migration policing.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 9, 2021).
Keywords: Border patrols -- Great Britain; Emigration and immigration law -- Great Britain; Border security -- Great Britain